Uso energético de la biomasa a través del proceso de gasificación (2017)
In this article, a review about thermochemical processes for energy recovery of biomass is made with special attention to the gasification process. This work articulates fundamental concepts and operational parameters of the gasification that define the quality and quantity of gaseous biofuels generated in the process. A description of the procedures of characterization of biomass for gasification processes and the optimal working conditions is made, specifying the advantages and disadvantages of the gas-producing agents. Subsequently, the stages of the process and the types of gasifiers and catalysts are exhibited.